Optimalisasi Sosialisasi Pemanfaatan Aspek Hukum Kepada Pelaku Usaha UMKM Desa Sukaratu Kecamatan Cikeusal Kabupaten Serang - Walid Mujtahidin; Fitria Agustin (STIKes Ibnu Sina Ajibarang, 2023)
Community Service carried out in this activity is a special form of community service activity that prioritizes three principles, namely education or teaching, research and community service. Implementation of Incidental Service Activities in 2023 with the theme